A phase 1 study of buparlisib and bevacizumab in patients with metastatic renal cell carcinoma progressing on vascular endothelial growth factor‐targeted therapies. Issue 15 (19th May 2016) - McKay, Rana R.; De Velasco, Guillermo; Werner, Lillian; Bellmunt, Joaquim; Harshman, Lauren; Sweeney, Christopher; Rosenberg, Jonathan E.; Hirsch, Michelle; Signoretti, Sabina; Van Allen, Eliezer M.; Walsh, Meghara; Vaishampayan, Ulka; et al.
Abstract : BACKGROUND: The phosphatidylinositol‐3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is dysregulated in patients with metastatic renal cell carcinoma (mRCC). Buparlisib is a pan‐PI3K inhibitor with activity in advanced solid tumors. The primary objective of the current study was to determine the maximum tolerated dose (MTD) and dose‐limiting toxicities of buparlisib and bevacizumab in patients with mRCC. Secondary objectives included efficacy, biomarker discovery, and additional toxicity. METHODS: This was a standard 3 + 3 dose escalation study of buparlisib (at a dose of 60‐100 mg/day) and bevacizumab (at a dose of 10 mg/kg every 2 weeks). After the MTD was defined, 15 patients were accrued to the expansion cohort. RESULTS: Thirty‐two patients were accrued (3 were treated at 60 mg/day, 21 were treated at 80 mg/day, 6 were treated at 100 mg/day, and 2 patients never received therapy). The majority of patients had clear cell histology (87%) and 50% had received ≥2 prior lines of therapy. The MTD of buparlisib was 80 mg/day and that of bevacizumab was 10 mg/kg every 2 weeks. A total of 28 patients discontinued therapy: 17 because of disease progression, 7 because of toxicity, and 4 for other reasons. Dose‐limiting toxicities included rash/pruritis, elevated lipase/amylase, anorexia, and psychiatric disorders (suicidal ideation, depression, and cognitive disturbances). Of the 30 patients who received at least 1 dose, 13% achieved a partial response (95% confidence interval, 4%‐31%). Two patients harboring activating PI3KA mutations achieved 42% and 16% maximal tumor shrinkage, respectively. CONCLUSIONS: Buparlisib at a dose of 80 mg/day with bevacizumab was found to be a tolerable regimen with preliminary activity in vascular endothelial growth factor‐refractory mRCC. The benefit of this combination may be of interest for future mRCC trials, possibly in a selected patient population. Cancer 2016;122:2389–2398 . © 2016 American Cancer Society . Abstract : The phosphatidylinositol‐3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is dysregulated in patients with metastatic renal cell carcinoma (mRCC), and targeting this pathway, in addition to the vascular endothelial growth factor (VEGF) pathway, is a potential therapeutic strategy in the management of RCC. Buparlisib at a dose of 80 mg/day with bevacizumab appears to be a tolerable regimen with preliminary activity in patients with vascular endothelial growth factor‐refractory mRCC.